Study of Flood Control Due To Land Use Change at the Estuary of Bang River, Malang - Syaiful, Amrie; Dermawan , Very; Purwati, Endang (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2023)
Water offers many advantages that are essential for the preservation of human existence. Excessive quantities of water, such as flooding, can negatively impact human beings. The land utilization within a watershed (drainage area) plays a crucial role in the frequency and impact of flooding events. Instances of land use changes that resulted in flooding happened in the Bang Sub-watershed, located in Malang Regency. A comprehensive and up-to-date examination of flood management solutions is required. This study seeks to offer technical suggestions for flood management in the Bang Sub-watershed due to land-use alterations, utilizing the HEC-RAS software. Integrated treatment solutions are provided to mitigate the potential damage caused by future flooding. The flood simulation yielded recommendations for mitigating the impact of future floods. These recommendations include the construction of a retarding basin in the upper part of the river with a capacity of 1.4 million m3, as well as the construction of a 654 m long river embankment that is 50 cm. The alteration of the land leads to a decrease in the cross-sectional capacity of the river at the mouth of the Bang River, resulting in annual flooding occurrences. A non-technical approach to enhance the quality of the watershed is implementing reforestation measures to decrease the runoff coefficient.